Ayurvedic Management of Moderate Depressive Disorder- A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Depressive disorders are highly prevalent mental disorders characterized by sadness, loss of interest or pleasure, feelings of guilt or low self-esteem, disturbed sleep or appetite, feelings of tiredness and poor concentration. About 300 million people are estimated to suffer from depression at a global level and in India the figures approximate to about 45.7 million. As per WHO, depression will be the leading cause of burden of disease by 2030 and the prevalence, incidence, and the morbidity risk of depression appears to be more in females than males.A 42-year-old lady presented with primary concerns of increased thoughts, decreased sleep, discomfort in stomach, abdominal distension, increased fatigue, decreased appetite and increased tension. Detailed interview with her husband and parents revealed that she had increased thoughts, slowness in performing activities, inability to do day to day works, reduced memory and concentration, increased anger towards her husband, mother and daughter, reluctance to have food and reduced social mingling. Based on the observations made in the level of affective and behavioural domains, diagnosis of depressive disorder - current episode moderate was eventually done as per the diagnostic criteria mentioned in International Classification of Disease 10.In Ayurveda, the condition was diagnosed as Kaphaja Unmada based on the typical symptoms. The treatment protocol including Snehapana, Vamana, Virechana and Vasthi was administered. The mental status of the patient was also addressed during the treatment period and Satvavajaya measures including individual and family counseling methods were administered. There was significant improvement in the Becks Depression Inventory score and Q – LES – Q – SF questionnaire after the intervention.